Optimalisasi Med-Sos Sebagai Alat Promosi Bisnis Online Bagi Ibu-Ibu Pokja Kelurahan Sukasari Tangerang - Narti Narti (Universitas Bina Sarana Informatika, 2024)
The mothers of POKJA kelurahan Sukasari Tangerang are community service partners for lecturers and students of Nusa Mandiri University for the 2022-2023 even academic year of the Narti group, M.Kom. The problem that exists with service partners is the desire of POKJA mothers to develop the community's economy, by directing residents, especially housewives who have little free time, to use their time to open a side business, on the basis of this desire, POKJA mothers want to provide counseling on how to promote, but still limited knowledge they have, for this reason, POKJA mothers ask Nusa Mandiri University lecturers to carry out community service in Sukasari village, so on this basis Nusa Mandiri University Lecturers and Students want to hold community service with the title